TRANSFORMATIONAL LEADERSHIP, MEANING IN WORK, LEADER MEMBER EXCHANGE (LMX), JOB PERFORMANCE DAN WORK ENGAGEMENT - Didik Joko Pitoyo; Hunik Sri Runing Sawitri (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2016)
The purpose of this study was to analyze the influence of meaning in work as intervening variable relationship between transformational leadership and work engagement and analyze the effect of work engagement as pemediasi variable relationship between leader-member exchange and job performance. This study uses a quantitative research methods. While the sample used this study as many as 213 people in the PT Kusumaputra Santosa Karanganyar. The data analysis techniques using multiple linear regression analysis method path.Results of this study are a) Transformational leadership significant effect on work engagement. b) Transformational leadership and meaning in work significant effect on work engagement. c) meaning in work can be a mediating variable and is expressed as a partial mediating variables (partial mediation). This is because, after entering the variable Meaning in Work, due to the influence of the variable Work Engagement Transformational Leadership which was significantly be remained significant after entering Meaning in Work variables into the regression equation model but declined regression coefficient. d) LMX significant effect on job performance. e) LMX and work engagement significant effect on job performance. f) Work engagement can be a mediating variable and is expressed as a partial mediating variables (partial mediation). This is because, the influence of variables leader member exchange for job performance that was significantly be remained significant after entering work engagement variable into the regression model but declined regression coefficient.